Interventions to Increase Blood Donation among Ethnic/Racial Minorities: A Systematic Review. (15th April 2019) - Makin, Jennifer K.; Francis, Kate L.; Polonsky, Michael J.; Renzaho, Andre M. N.
Abstract : Ethnic/racial minorities are under-represented in blood donor populations in most developed countries. This is of particular concern where minorities differ from a country's majority population in terms of blood or tissue typing, especially where type matching is required for effective management of rare disorders such as sickle-cell disease that require multiple transfusions. This systematic review assessed the effectiveness of interventions to increase blood donation among ethnic/racial minority populations in developed countries. We searched MEDLINE, EMBASE, CINAHL, and ProQuest on 20 March 2017 with no date restrictions and supplemented this with searches on Google Scholar, blood collection agency websites, reference lists of included studies, and a forward search of citations of included studies. We included intervention studies designed to increase recruitment and/or retention of adult, ethnic/racial minority blood donors in developed countries. The review identified eight studies reported in nine publications. Six were conducted in the USA with African Americans. Four studies reported on multifaceted, community-based interventions; three reported on one-off information and educational video interventions, presented face-to-face, or delivered via post or e-mail. The level of evidence for efficacy was low, and the majority of studies were assessed as having some risk of bias related to one or more methodological issues. All eight studies reported positive outcomes in blood donation and/or intention to donate. Seven trials found that the intervention increased presentation for donation, and three found an increase in the percentage of new donors from the ethnic minority targeted. The review findings demonstrate that it is possible to design and implement effective interventions to motivate individuals from ethnic/racial minority groups to donate blood. One-off interventions may be as effective as multifaceted, community-based interventions. There was insufficient evidence to recommend particular interventions, and future research should empirically assess alternative interventions using robust study designs.